Development of a Gelatin-Based Genomic Reference Material for Halal Authentication Using Real-Time PCR - Rahma, Anisa Aula; Meilani, Nanda Diva; Sulistiawati; Ainaputri, Aliza Salsabila; Damara, Dandy Satria; Malau, Jekmal (Science and Technology Indonesia, 2025)
Indonesia, home to over 270 million people, has the largest Muslim population globally, with approximately 87.18% adhering to Islam, driving significant demand for halal products, particularly in the food and pharmaceutical sectors. Gelatin, commonly used in medicinal capsules, often originates from porcine sources, necessitating precise halal authentication methods. This study presents the development of a novel genomic DNA-based Reference Material (RM) for gelatin, specifically for porcine DNA detection, employing Real-Time Polymerase Chain Reaction (qPCR) techniques. The methodology encompassed in-silico primer design, sample extraction optimization, DNA quality and quantity analysis, linearity assessment, limit of detection (LoD) and quantification (LoQ) determination, and RM characterization. Results indicated that the designed primers could reliably and efficiently detect porcine DNA, with optimal annealing at 58°C and primer concentration at 500 nM, achieving a PCR efficiency of 96.74%. The LoD and LoQ for pork meat samples were determined to be 0.02 pg/uL and 0.004 pg/uL, respectively, while the LoD for porcine gelatin was 0.27 ng/uL. The RMs exhibited robust homogeneity (Sig. 0.052), significant intergroup differences (Sig. 0.000), and low variation (CV 0.96%). Short-term storage at -80°C and -20°C preserved Ct value stability and consistency. Conclusively, this study successfully developed a novel gelatin-based genomic DNA RM for halal authentication, offering a scientifically validated tool that strengthens the halal assurance system, addressing Indonesian consumers’ demand for porcine-free products. These findings hold substantial implications for regulatory authorities, especially in Indonesia, and could inform the development of standardized qPCR RMs for porcine DNA detection in halal compliance testing.